Especificação de um sistema de informação para nomeação e exoneração de cargos comissionados no corpo de bombeiros militar do Estado do Pará. - MATOSO, Jamyson da Silva (2020)
Decision making by the manager of a public institution needs to be supported by a lot of information. For example, to appoint or remove an officer from a commissioned position requires some information about the military, such as: there is some legal impediment to exoneration or appointment on the day the manager intends to make such modifications at his command post. In order to assist in the decision-making of the Commander General of the Pará Military Fire Brigade (CBMPA), the institution's maximum manager, for the appointment and dismissal of commissioned positions, a specification was developed for the development of software that provides information to Officers and of the Commissioned Posts. This tool intends to be an additional resource to facilitate appointments and exonerations of Officers in the commissioned positions existing in the institution, allowing greater agility and security in the decision making, and also contributing to material savings, since several physical reports will no longer be issued to each act of appointment/exoneration.